1999
DOI: 10.1002/(sici)1521-3749(199909)625:9<1408::aid-zaac1408>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

An Expected Calcium Carbido Borate Chloride: Ca9Cl8(BC2)2

Abstract: structure structure (solids and liquids) D 2000 -014The Nitrido Borates Ln 3 B 2 N 4 (Ln: La-Nd) and La 5 B 4 N 9 : Syntheses, Structures, and Properties.-The compounds Ln 3 B 2 N 4 with Ln: La, Ce, Pr, and Nd are prepared by reaction of LnN, Ln, and hexagonal BN in a CaCl 2 flux (1500 K, 4 d). The isotypic compounds crystallize in the space group Immm with Z = 2. The compounds, which can also be formulated as (Ln 3+ ) 3 (B 2 N 4 8− ) (e − ), contain the oxalate analogue B 2 N 4 8− and one electron in the cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The Raman spectrum of the extremely bent (BC 2 ) 5− anion in Ca 9 (BC 2 ) 2 Cl 8 [7] with C 2v symmetry and the Raman as well as the IR spectrum of the (CBN) 4− anion with C ∞v symmetry observed in Ca 15 (CBN) 6 (C 2 ) 2 F 2 exhibit all three modes ν sym , ν asym and δ (the modes are -not in accordance with the real symmetry -named in analogy to triatomic moieties with D ∞v symmetry) expected for a triatomic unit due to the decrease in symmetry. It is noteworthy that the antisymmetric stretching mode was not observed in the Raman spectrum of the compound Ca 5 (BC 2 )(C 2 )Cl 3 [6] despite its similarity to Ca 9 (BC 2 ) 2 Cl 8 [7] regarding the symmetry and coordination of the (BC 2 ) 5− moiety.…”
Section: Optical Spectramentioning
confidence: 92%
See 3 more Smart Citations
“…The Raman spectrum of the extremely bent (BC 2 ) 5− anion in Ca 9 (BC 2 ) 2 Cl 8 [7] with C 2v symmetry and the Raman as well as the IR spectrum of the (CBN) 4− anion with C ∞v symmetry observed in Ca 15 (CBN) 6 (C 2 ) 2 F 2 exhibit all three modes ν sym , ν asym and δ (the modes are -not in accordance with the real symmetry -named in analogy to triatomic moieties with D ∞v symmetry) expected for a triatomic unit due to the decrease in symmetry. It is noteworthy that the antisymmetric stretching mode was not observed in the Raman spectrum of the compound Ca 5 (BC 2 )(C 2 )Cl 3 [6] despite its similarity to Ca 9 (BC 2 ) 2 Cl 8 [7] regarding the symmetry and coordination of the (BC 2 ) 5− moiety.…”
Section: Optical Spectramentioning
confidence: 92%
“…For comparison, the Raman spectra of the compounds Ca 5 (BC 2 )(C 2 )Cl 3 [6] and Ca 9 (BC 2 ) 2 Cl 8 [7] were recorded on single crystals in Mark capillaries sealed under a protective argon atmosphere (microscope laser Raman spectrometer: Jobin Yvon, 4 mW, excitation line at λ = 632.817 nm (HeNe laser), 100× magnification, 6 × 30 s accumulation time) since these had not been reported yet (Fig. 2).…”
Section: Raman and Ir Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…[52] It was found that different polymorphic structures could coexist. [53] The phase transitions and ratios depend on the reaction temperature, size of the crystallites, proportions and type of reactants, [54] and purity of the sample. [55] In 2010, three new possible metastable structures were predicted to form at standard pressures (Figure 9d and e) and at high pressures ( Figure 9f).…”
Section: Structure and Properties Of Calcium Carbidementioning
confidence: 99%